Study of NAP adsorption and assembly on the surface of HOPG - Korolkov, Vladimir V.; Allen, Stephanie; Roberts, Clive J.; Gozes, Illana; Tendler, Saul J.B. (Elsevier, 2014)
NAP is an octapeptide that has demonstrated a neuroprotective/therapeutic efficacy at very low concentrations in preclinical studies and in a number of clinical trials. Yet little is known about its structural organization at low concentrations. Here, we have employed atomic force microscopy to investigate NAP peptide assembly on graphite in aqueous media at nanomolar concentration. High spatial resolution scans of NAP assemblies reveal their fine structure with clearly resolved single NAP units. This observation leads us to conclude that NAP molecules do not form complex self-assembled structures at nanomolar concentration when adsorbed on graphite surface.